Integrational Justice: South America’s Experience - Georgy V. Alekseev; Artur A. Gapeev (Евразийская интеграция: экономика, право, политика, 2019)
Integration justice is the result of supranational courts work in the framework of states’ regional economic unions. The resolution of disputes between states, supranational institutions and economic entities in the framework of the common market of South American countries (Mercosur) and the Andean community is of considerable interest in terms of comparative analysis of similar practices in the European Union and the Eurasian Economic Union. The international integration practice has shown that the legal force, binding nature and direct action of decisions of supranational courts are necessary to bring the national legal systems of the member states of integration associations to a harmonized rule of law.